The Diverse Cellular and Animal Models to Decipher the Physiopathological Traits of Mycobacterium abscessus Infection - Bernut, Audrey; Herrmann, Jean-Louis; Ordway, Diane; Kremer, Laurent (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium abscessus represents an important respiratory pathogen among the rapidly-growing non-tuberculous mycobacteria. Infections caused by M. abscessus are increasingly found in cystic fibrosis patients and are often refractory to antibiotic therapy. The underlying immunopathological mechanisms of pathogenesis remain largely unknown. A major reason for the poor advances in M. abscessus research has been a lack of adequate models to study the acute and chronic stages of the disease leading to delayed progress of evaluation of therapeutic efficacy of potentially active antibiotics. However, the recent development of cellular models led to new insights in the interplay between M. abscessus with host macrophages as well as with amoebae, proposed to represent the environmental host and reservoir for non-tuberculous mycobacteria. The zebrafish embryo has also appeared as a useful alternative to more traditional models as it recapitulates the vertebrate immune system and, due to its optical transparency, allows a spatio-temporal visualization of the infection process in a living animal. More sophisticated immunocompromised mice have also been exploited recently to dissect the immune and inflammatory responses to M. abscessus. Herein, we will discuss the limitations, advantages and potential offered by these various models to study the pathophysiology of M. abscessus infection and to assess the preclinical efficacy of compounds active against this emerging human pathogen.